3D echocardiographic reference ranges for normal left ventricular volumes and strain: results from the EACVI NORRE study. (22nd December 2016) - Bernard, Anne; Addetia, Karima; Dulgheru, Raluca; Caballero, Luis; Sugimoto, Tadafumi; Akhaladze, Natela; Athanassopoulos, George D.; Barone, Daniele; Baroni, Monica; Cardim, Nuno; Hagendorff, Andreas; Hristova, Krasimira; et al.
Abstract : Aim: To obtain the normal ranges for 3D echocardiography (3DE) measurement of left ventricular (LV) volumes, function, and strain from a large group of healthy volunteers. Methods and results: A total of 440 (mean age: 45 ± 13 years) out of the 734 healthy subjects enrolled at 22 collaborating institutions of the Normal Reference Ranges for Echocardiography (NORRE) study had good-quality 3DE data sets that have been analysed with a vendor-independent software package allowing homogeneous measurements regardless of the echocardiographic machine used to acquire the data sets. Upper limits of LV end-diastolic and end-systolic volumes were larger in men (97 and 42 mL/m 2 ) than in women (82 and 35 mL/m 2 ; P < 0.0001). Conversely, lower limits of LV ejection fraction were higher in women than in men (51% vs. 50%; P < 0.01). Similarly, all strain components were higher in women than in men. Lower range was −18.6% in men and −19.5% in women for 3D longitudinal strain, −27.0% and −27.6% for 3D circumferential strain, −33.2% and −34.4% for 3D tangential strain and 38.8% and 40.7% for 3D radial strain, respectively. LV volumes decreased with age in both genders ( P < 0.0001), whereas LV ejection fraction increased with age only in men. Among 3DE LV strain components, the only one, which did not change with age was longitudinal strain. Conclusion: The NORRE study provides applicable 3D echocardiographic reference ranges for LV function assessment. Our data highlight the importance of age- and gender-specific reference values for both LV volumes and strain.